Ekosistem pendidikan antikorupsi di Perguruan Tinggi Keagamaan Islam Negeri - Abdul Kholiq; Kartika Indah Permata (Komisi Pemberantasan Korupsi, 2023)
The corruption crisis in Indonesia has reached a dangerous level and must receive attention from all parties, including higher education institutions. Otherwise, it could lead to destruction in Indonesia. Despite focusing merely on describing anticorruption education ecosystems in religious universities, this study is significant for Indonesia's sustainable growth. Hence, this research aims to identify anticorruption education ecosystems at State Islamic Universities (PTKIN) in Indonesia. Using a descriptive quantitative method, the data was collected through a questionnaire with the indicators: (1) anticorruption value-creating networks; (2) a clean and transparent governance system, and (3) collective awareness of the need for a movement to fight corruption (shared logic). The questionnaire was distributed to Vice Rectors II (general administration, planning and finance) and the Heads of the SPI (Internal Supervisory Unit) at PTKIN. The results of this research proved that the characteristics of the educational ecosystem at PTKIN were quite supportive of anticorruption education, with an average score of 3.4833 (score category C). This finding still did not meet community expectations. Therefore, to create a better anticorruption education ecosystem, tighter laws and dedication from PTKIN leadership were required.